Multiple Cranial Organ Defects after Conditionally Knocking Out Fgf10 in the Neural Crest - Teshima, Tathyane H. N.; Lourenco, Silvia V.; Tucker, Abigail S. (Frontiers in Physiology, 2016)
Fgf10 is necessary for the development of a number of organs that fail to develop or are reduced in size in the null mutant. Here we have knocked out Fgf10 specifically in the neural crest driven by Wnt1cre. The Wnt1creFgf10fl/fl mouse phenocopies many of the null mutant defects, including cleft palate, loss of salivary glands and ocular glands, highlighting the neural crest origin of the Fgf10 expressing mesenchyme surrounding these organs. In contrast tissues such as the limbs and lungs, where Fgf10 is expressed by the surrounding mesoderm, were unaffected, as was the pituitary gland where Fgf10 is expressed by the neuroepithelium. The circumvallate papilla of the tongue formed but was hypoplastic in the conditional and Fgf10 null embryos, suggesting that other sources of FGF can compensate in development of this structure. The tracheal cartilage rings showed normal patterning in the conditional knockout, indicating that the source of Fgf10 for this tissue is mesodermal, which was confirmed using Wnt1cre-dtTom to lineage trace the boundary of the neural crest in this region. The thyroid, thymus and parathyroid glands surrounding the trachea were present but hypoplastic in the conditional mutant, indicating that a neighbouring source of mesodermal Fgf10 might be able to partially compensate for loss of neural crest derived Fgf10.